Antimicrobial use in developing countries - Grace, Delia; Lindahl, Johanna F.; Hung Nguyen-Viet; Kakkar, M. (International Livestock Research Institute, 2015)
We conducted a study on agriculture related antimicrobial resistance (AMR) in developing countries. AMR pathogens are commonly found in animals, animal food products and agro-food environments, but the lack of surveillance systems means there are no reliable national data on the level of AMR in animals and their products. While AMR infections in animals and their products contribute to AMR infections in people in developing countries the literature is insufficient to draw firm conclusions on the extent of this contribution, which is likely to vary in different contexts. For example, a recent study found high levels of multi-drug resistance in goats kept by pastoralists in remote, isolated areas and never given treatments by veterinarians or farmers. The key driver of agriculture-related AMR is the quantity and quality of use of antimicrobials in livestock production and aquaculture. In developing countries as much as several hundred thousand tons may be used every year, agricultural use probably exceeds medical use, and most use is probably in intensive systems. The underlying driver for antimicrobial use and development of AMR is the livestock and aquaculture revolution that is the rapid growth in intensive production systems in response to increased demand for livestock and fish products. Based on livestock intensification patterns, China, Brazil and India are current hotspots, and future hotspots with fastest growth of the intensive livestock sector in Myanmar, Indonesia, Nigeria, Peru and Vietnam. China is a hotspot for aquaculture and Indonesia, Thailand, Vietnam, Bangladesh, India and Chile are other countries where antimicrobial use in fish production may be problematic. AMR is intrinsically a global problem that can only be managed at supra-national scale and the current strong momentum to take action on AMR provides an opportunity to address the problem globally and comprehensively, addressing medical and veterinary use. This will require better evidence on the use of antimicrobials in agriculture, the impacts of this use on human and animal health, the acceptability and feasibility of stricter control of antibiotic use in agriculture, and the costs and benefits of stricter control taking into account trades offs between overuse and lack of access to antimicrobial drugs.